State Racism and Surveillance in Xinjiang (People's Republic of China) - Gerald Roche; James Leibold (2022)
Abstract: Racism, as a truly global phenomenon, requires a comparative approach that can account for its diverse forms and their commonalities. Despite the prevalence and relevance of racism throughout Asia, much scholarship on the topic remains parochially focussed on the north Atlantic world. This article aims to help address this issue in two ways. First, it discusses surveillance and racialisation practices in the Xinjiang Uyghur Autonomous Region in China, based on an examination of leaked police files from the city of Urumqi. It examines how racialisation processes are carried out through surveillance, who these impact, and how. Second, these empirical materials are put in a broader comparative framework, drawing on Michel Foucault's concept of state racism, which sees racism as a technique of governance common to all contemporary states. The conclusions reflect on what it means to undertake anti-racist scholarship in a world of racist states.